Análise espacial da evolução socioeconômica dos municípios sobre a demanda do sistema de transporte público de passageiros do Ceará - Aguiar, José Roberto Sales de (2015)
The Socioeconomics of Ceará suffered enormous changes over the past decade, with a reduction of social inequality due to changes in state intervention policies. As the Intermunicipal System of Transport of Passengers of Ceará (STIP-CE) was planned according to the reality of the early 2000s, it is assumed that the current offer does not meet the requisites of mobility and accessibility for passengers. Also, as Transport is a eminently geographical phenomenon, it is necessary to use the spatial statistics tools to analyze it. However, problems in the implementation of these tools were found in the compilation of data, derived from the lack of consolidated method on the subject. Thus, the general objective of this master thesis research is to analyze the changes in the spatial pattern of the passengers demand for intercity public transportation from socioeconomic changes in the municipalities of Ceará in the 2000s, applying the exploratory spatial analysis tools to verify the hypotheses that (i) the increase in the income of individuals influences the increase of trip by private transportation and therefore reduces the demand for trip by public transport; and (ii) reducing the differences in economic activity of municipalities, which expresses the reduction in polarizing power, impacts on reducing trip by public transportation. To this end a method to use these tools has been proposed, as well as a georeferenced database was compiled. The results of its application shows further evidence that the hypothesis that there is no relationship between socioeconomic development and demand for transport can be rejected, as observed by correlation between these phenomena, especially around the metropolitan area of Fortaleza for both regional and radial trips. There are some places, however, that should be analyzed according to their socioeconomic characteristics and level of service offered (like Sobral/Ibiapaba and west of the Litoral Oeste for regional trip and Cariri, for radial). As recommendations, it is noted (i) that the proposed method can be supplemented, (ii) there should be greater accuracy in the collection of STIP-CE demand data from the Ceará Government and (iii) the method hereby proposed should be given continuity in order to quantify the relationships between phenomena and test hypotheses of its existence by local confirmatory models